Preliminary framework of topology control algorithm in WSN to achieve node's energy efficiency - Shahabuddin, M.Z. (Institute of Electrical and Electronics Engineers Inc., 2016)
Wireless sensor network (WSN) node is developed based on IEEE 802.15.4 consists of low-rate capacities i.e. limited power source and communication capabilities, somehow expected to operate at relatively long time in harsh environment. The objective of this paper is to propose fundamental modelling of topology control algorithm to conserve individual WSN node's energy, and at the same time preserving the graph connectivity. The proposed topology control algorithm consists of three phases: 1. Identifying connecting nodes at maximum transmission, 2. Pairing nodes with shortest algorithm/minimum-energy level, 3. Calculating/setting minimum power transmission per-node for energy conservation. The algorithm works-out locally and dispenses full graph connectivity, and theoretically would be able to reduce WSN control overhead. Â© 2016 IEEE.